Ala519Thr mutation in exon 11 of LDL receptor gene in members of a Malaysian family with hypercholesterolaemia - Junit, S.M.; Othman, S.; Yusof, Rohana; Billett, M.A.; Harun, F. (2003)
We report a case of a Familial Hypercholesterolaemic (FH) patient (FH1) and her family members. They are Malaysian of Indian origin with evidence of consanguinity in the parents. We characterised the LDL receptor gene mutation in FH1, her brother (S1) and their mother, P2. The father (P1) died of coronary heart disease (CHD) in his early 40âs. Our investigation reveals that FH1 and her family do not carry the two of the major known Familial Defective ApoB mutations, Arg3500Gln and Arg3531Cys. Sequencing analysis of the LDL receptor gene demonstrated that FH1 is homozygous for a G to A substitution at nucleotide position 1618, which causes the amino acid to change from alanine to threonine at position 519 (A519T). Both the mother and the eldest brother (S1) of FH1 are heterozygous for the A519T mutation. The A519T mutation had been previously reported in Western ethnicity of the United Kingdom, German and Icelandic origin but this is the first to be identified in the Asian region.